Native Non-Saccharomyces Yeasts as a Tool to Produce Distinctive and Diverse Tamjanika Grape Wines - Ivana Karabegović; Marko Malićanin; Nikola Popović; Sandra Stamenković Stojanović; Miodrag Lazić; Jelena Stanojević; Bojana Danilović (Foods, 2022)
The enological potential of two previously characterized indigenous yeast isolates, Hanseniaspora uvarum S-2 and Candida famata WB-1, in pure and sequential inoculation with commercial yeast Saccharomyces cerevisiae QA23 were analyzed in industrial-scale vinification of the grape variety Tamjanika. Their contribution to the quality and aroma profile was investigated by quantifying volatile compounds and wine sensory evaluation. Both yeast isolates were able to complete alcoholic fermentation, to reduce ethanol concentration up to 1.06% v/v (in monoculture) in comparation to S. cerevisiae QA23, and to enhance aroma and sensory profile. Based on calculated odor activity values (OAV), p-cymene, ethyl hexanoate, ethyl octanoate, and ethyl decanoate were the major aroma volatile compounds in all Tamjanika wine samples. Analyzed yeast strains significantly affected relative contribution of volatile compounds and can be considered responsible for the differences and uniqueness of the obtained wine samples. Besides confirmation of good enological and fermentative characteristics, selected isolates can be characterized as high ester-producing strains with potential to enhance the floral and fruity aromas of wine. The present study represents a further step toward the use of indigenous yeast isolates at industrial-scale fermentation in order to ensure the regional signature of Tamjanika wine.